Recensione a K. Östlund, Johan Ihre on the Origins and History of the Runes, Uppsala 2000 - Cucina, Carla (Classiconorroena, 2016)
Recensione a K. Östlund, Johan Ihre on the Origins and History of the Runes, Uppsala 2000.